ASSOCIATION OF DIFFERENT PARAMETERS OF COMPLETE BLOOD COUNT WITH SEVERITY AND PROGNOSIS OF GUILLAIN-BARRE SYNDROME - Aziz, Nauman; Khan, Humera; Jafri, Syeda Rizwana; Qureshi, Fauzia; Muneeb, Amna; Akif, Ursula (Pakistan Armed Forces Medical Journal, 2021)
Objective: Guillain-barré syndrome is the most common and most severe acute paralytic neuropathy. This study is also aimed at to know that if there is any association of parameters of complete blood count and whether these can be used as a prognostic marker for guillain-barré syndrome.Study Design: Retrospective cross-sectional.Place and Duration of Study: Sahiwal Medical College Sahiwal, from Oct 2019 to Aug 2020.Methodology: This retrospective cross-sectional study was conducted at Sahiwal Medical College Sahiwal, from Oct 2019 to Aug 2020 after approval from Institutional Review Board. The data was assessed by SPSS-26. Frequency distributions of study participants were calculated. Significance of the associations was assessed by Kruskal-Wallis test and one way ANOVA test. A p-value